Moral Economic Transitions in the Mongolian Borderlands A proportional share - Waters, Hedwig Amelia (Economic Exposures in Asia, 2023)
Since the early 1990s, Mongolia began its hopeful transition from socialism to a market democracy, becoming increasingly dependent on international mining revenue. Both shifts were promised to herald a new age of economic plenty for all. Now, roughly 30 years on, many of Mongolia's poor and rural feel that they have been forgotten. Moral Economic Transitions in the Mongolian Borderlands describes these shifts from the viewpoint of the self-proclaimed 'excluded': the rural township of Magtaal on the Chinese border. In the wake of socialism, the population of this resource-rich area found itself without employment and state institutions, yet surrounded by lush nature 30 kilometres from the voracious Chinese market. A two-tiered resource-extractive political-economic system developed. Whilst large-scale, formal, legally sanctioned conglomerates arrived to extract oil and land for international profits, the local residents grew increasingly dependent on the Chinese-funded informal, illegal cross-border wildlife trade. More than a story about rampant capitalist extraction in the resource frontier, this book intimately details the complex inner worlds, moral ambiguities and emergent collective politics constructed by individuals who feel caught in political-economic shifts largely outside of their control. Offering much needed nuance to commonplace descriptions of Mongolia's post-socialist transition, this study presents rich ethnographic detail through the eyes and voices of the state's most geographically marginalized. It is of interest not only to experts of political-economy and post-socialist transition, but also to non-academic readers intrigued by the interplay of value(s) and capitalism.